Major depressive disorder elevates the risk of dentofacial deformity: a bidirectional two-sample Mendelian randomization study - Nie, Jinhan; Zhang, Yi; Ma, Jun; Xue, Qing; Hu, Min; Qi, Huichuan (Frontiers in Psychiatry, 2024)
The association between psychiatric disorders and dentofacial deformities has attracted widespread attention. However, their relationship is currently unclear and controversial.A two-sample bidirectional MR analysis was performed to study the causal relationship between dentofacial deformity and eight psychiatric disorders, including major depressive disorder, panic disorder, schizophrenia, bipolar disorder, attention deficit hyperactivity disorder, Alzheimer's disease, autism spectrum disorder, and neuroticism.Inverse variance weighted, weighted median, MR-Egger regression, weighted mode four methods, and further sensitivity analyses were conducted.The major depressive disorder affected dentofacial deformity, with an OR = 1.387 (95% CI = 1.181-1.629, P = 6.77×10 -5 ). No other psychiatric disorders were found to be 2 associated with dentofacial deformity. In turn, dentofacial deformity were associated with neuroticism, with an OR = 1.050 (95% CI = 1.008-1.093, P = 0.018). And there was no evidence that dentofacial deformity would increase the risk of other psychiatric disorders.Major depressive disorder might elevate the risk of dentofacial deformities, and dentofacial deformity conditions would increase the risk of the incidence of neuroticism.